Aqueous extract of large cardamom inhibits vascular damage, oxidative stress, and metabolic changes in fructose-fed hypertensive rats - Kanthlal SK; Arya VS; Bindhu Paul–Prasanth; Vijayakumar M; Rema Shree AB; Uma Devi P (Clinical and Experimental Hypertension, 2021)
Purpose Since metabolic abnormalities such as elevated glucose level and imbalanced lipid profiles increase the risk for hypertension and cause endothelial dysfunction, we evaluated the effect of aqueous extract of large cardamom (AELC) on fructose-induced metabolic hypertension and oxidative stress Methods The male Sprague-Dawley rats were divided into 6 groups with 5 rats in each group, and each group was fed with 10% fructose in drinking water for 8 weeks. Starting from week 5, animals were treated with 50, 100, and 200 mg/kg/day AELC or Losartan (10 mg/kg/day). Systolic, diastolic, and mean arterial blood pressure was measured once in every seven days using the tail-cuff method. Vascular function, plasma nitric oxide (NO), glucose, lipid profiles, serum biochemical, and anti-oxidant parameters were also evaluated. Results Rats fed with fructose showed higher blood pressure, serum cholesterol, and triglyceride levels, but decreased in the AELC or Losartan treatment group. Treatments with AELC prevented exaggerated plasma glucose and oxidative stress and restored the nitric oxide level in fructose-fed rats. Besides, it also reduced vascular proliferation and improved the relaxation response of acetylcholine in the aorta pre-contracted with phenylephrine. Conclusion In summary, the obtained results suggest that AELC can prevent and reverse the high blood pressure induced by fructose, probably by restoring nitric oxide level and by improving altered metabolic parameters.